Genetic analysis of threshability in grain sorghum [Sorghum bicolor (L.) Moench]. Issue 2 (16th January 2015) - Adeyanju, Adedayo; Perumal, Ramasamy; Tesso, Tesfaye; Pillen, K.
Abstract The ease with which seeds are detached from panicles is one of the early domestication traits. Genotypes with sticky panicles are hard to thresh, and whenever threshed, the grain tends to remain attached to the glume which reduces market value and processability. This study was conducted to determine the genetic mechanisms underlying the threshability trait in sorghum. Four seed parents and eleven pollinators differing for threshability were intercrossed in Design II mating scheme and the resulting hybrids and the parents were grown in four environments. Threshability was estimated as the ratio of seed yield to panicle weight (TW) and proportion of seeds without sticky glumes (TG). Variation was significant among the entries, inbreds and hybrids with GCA for TG and TW varying markedly. Mean TG for inbred and hybrids of low threshable genotypes was not markedly different indicating that threshability trait is under the control of additive genes with dominant or partially dominant effects. Segregation analysis indicates that the TG trait may be under the control of few major genes with approximately one to three loci affecting the trait.